Avaliação do efeito da vacinação BCG na reação do Teste Tuberculínico (TT) nos dois primeiros anos de vida - Kurtz, Tatiana (2017)
Introduction and Objectives: Tuberculosis (TB) is a complex infectious disease that can occur in any age group. When the host comes in contact with Mycobacterium tuberculosis (MTB) the immune response of the organism may be sufficient to prevent the disease, resulting in total destruction of the bacteria or establishment of latency, termed latent tuberculosis (TBL). Due to the difficulty in demonstrating MTB in the clinical specimens of the child, the diagnosis of TB disease is based on the clinical, epidemiological and radiological bases associated with the interpretation of the cutaneous tuberculin (TT) test. In this context, Mycobacterium tuberculosis infection, mostly latent, represents an important reservoir for reactivation of the disease. This contingent is sufficient to continue generating new cases for many decades, even if the chain of transmission is interrupted. Thus, the precise definition of the criteria for diagnosis of latent TB has great relevance and TT is an important tool. The objective of the study is to evaluate the effect of the neonatal BCG vaccine on the tuberculin skin test cutaneous reaction and to define cutoff points to detect tuberculosis in the first two years of life. Methods: A cross-sectional study was carried out in children from the municipality of Santa Cruz do Sul, who met the inclusion criteria of the study: infants up to 2 years of age who received BCG vaccine during the neonatal period. Exclusion criteria were birth weight <2,000 grams, being the mother of HIV positive mother, or mother with persistence of tuberculosis in the perinatal period, or cases where there was evidence of primary immunodeficiency, absence of BCG vaccine scar after 6 months of life, in addition to TB research and TB contact. The children were identified and included through the authorization of the person responsible, explaining the project and accepting the consent term. The project was approved by the Research Ethics Committee of the Santa Cruz Hospital, where patient data were collected and the University of Santa Cruz do Sul (UNISC). The variable under study was the cutaneous induration reaction of the tuberculin test, in the first two years post-vaccination, using different cutoff points. A descriptive analysis of the variables was performed. Numerical variables were represented by mean and standard deviation and categorical variables by means of absolute number and percentage. To describe the data, we used means and standard deviation, or median and interquartile range for the quantitative variables; percentage for qualitative variables. For analysis of the Tuberculin Test, the sample was submitted to the analysis of variance (ANOVA), with significance level of p≤0.05. The data analyzed in the SPSS Program 17.0. Results: Potentially eligible participants totaled 808, of which 90 were selected from the inclusion / exclusion criteria. Data collected included demographic characteristics, nutritional indexes, vaccination status and previous exposure to TB. TTs were administered and induration measured after 48-72 hours. The selected ones were of both sexes, with ages varying between 3 and 24 months. Of these, eleven were excluded because they did not attend the reading of the tuberculin test (TT), resulting in a sample of 79 patients. The median age was 9.5 months for boys and 11 months for girls. It was divided into 3 groups according to the age range: between 3-9 months (group 1), 10-18 months (group 2) and 19-24 months of age (group 3). We found that, when comparing the 3 groups, we showed a decrease in the mean response to tuberculin as the age group progresses, presenting statistical significance (p = 0.041). Considering the probable absence of Mycobacterium tuberculosis infection in the sample of patients included in the study, we observed that the tuberculin test with the highest reaction occurs in group 1. From the age of 10 months, no patient shows a reaction to the tuberculin test above 5 mm. The finding shows the decline in the tuberculin reaction curve in the first year of life. A complementary analysis was performed excluding patients who did not present an induration reaction (TT = 0 mm), and 28 patients were excluded from the interpretation. The 51 patients with Test Tuberculin reactor were divided into the same 3 groups according to age group. Between 3-9 months (group 1), 10-18 months (group 2) and 19-24 months of age (group 3), we found that when comparing the 3 groups, again we showed a decrease in the reaction to tuberculin according to age progresses, presenting significance (p = 0.031). We found that there were no adverse effects, described in the literature, in patients who underwent the Tuberculin Test. Conclusions: Based on the data from the study, we demonstrated that the induration reaction occurs in the tuberculin test in the first 12 months of age in previously healthy and BCG-vaccinated patients in the neonatal period. Therefore our results suggest that the cutoff point could be modified from 10mm to 5mm of induration after 12 months of age, improving the specificity of the TT diagnostic test to identify cases of TB infection. This reevaluation of the lowest cutoff point in the first two years of life may prevent inappropriate management in patients with tuberculosis.